Regional economic integration in the pacific: An empirical study - Jayaraman T.K.; Lee H.-H.; Lee H.-A. (2023)
The Pacific Islands Forum, the regional organization comprising 14 Pacific Island countries (PICs), Australia and New Zealand is committed to strengthen regional cooperation and integration. This paper examines progress in real and financial integration in the region. Utilizing the methodology based on international parity conditions: purchasing power parity and uncovered interest parity, the study concludes that while PICs' integration amongst themselves and with Australia and New Zealand, is relatively advanced with respect to goods and services, the financial market integration remains incomplete. The policy implication is impact of further liberalization is likely to be substantial on financial markets. 2006 Institute of East and West Studies, Yonsei University, Seoul.